Nowcasting GDP in Real-Time: A Density Combination Approach - Knut Are Aastveit; Karsten R. Gerdrup; Anne Sofie Jore; Leif Anders Thorsrud (Norges Bank, 2011)
In this paper we use U.S. real-time vintage data and produce combined density nowcasts for quarterly GDP growth from a system of three commonly used model classes. The density nowcasts are combined in two steps. First, a wide selection of individual models within each model class are combined separately. Then, the nowcasts from the three model classes are combined into a single predictive density. We update the density nowcast for every new data release throughout the quarter, and highlight the importance of new information for the evaluation period 1990Q2-2010Q3. Our results show that the logarithmic score of the predictive densities for U.S. GDP increase almost monotonically as new information arrives during the quarter. While the best performing model class is changing during the quarter, the density nowcasts from our combination framework is always performing well both in terms of logarithmic scores and calibration tests. The density combination approach is superior to a simple model selection strategy and also performs better in terms of point forecast evaluation than standard point forecast combinations.
hdl:11250/2496950
Keywords: C32; C52; C53; E37; E52; 330; density combination; forecast densities; forecast evaluation; monetary policy; nowcasting; real-time data